(untitled) (Revista Educação, Artes e Inclusão, 2021)
We describe an investigation in the area of ​​special music education with the use of active methods for students with intellectual disabilities (ID). The work shows the benefits provided using actions inspired by the active methods for the general development of learners, including aspects related to cognition, motor and social interaction. The objective of the research was to understand the applicability of the active methods in music classes with intellectually deficient students. The methodology used was autoethnography, which describes a personal experience and seeks to reveal knowledge from within a phenomenon, showing aspects that cannot always be accessed in conventional research. We described three models of lessons applied in three different classes and analysed the objectives of the lessons, the used methods and the results. We consider the use of active methods with intellectual disabilities as a viable resource that benefits the development of musical and extramusical skills that can assist in improving student’s quality of life.